Rocca San Silvestro - MINUTOLI, GIOVANNI (Firenze University Press, 2022)
This volume collects five years of studies conducted by various researchers coordinated by the author and describe the different phases of the restoration project and the construction site of Rocca San Silvestro. The restoration project developed in the awareness that the site needed, not just a set of technical operations, but also of a critical act that led to the drafting of a project not only reversible, recognizable and compatible but above all a sustainable restoration. This is to be considered as a moment of confrontation between archaeologists and architects and follows on from the book written by Andrea Arrighetti, Rocca San Silvestro: Archeology for the restoration, published in 2017.